The role of transitional justice in promoting human rights (قضايا سياسية, 2024)
Transitional justice is a set of mechanisms taken by society and the state for the purpose of addressing human rights violations caused by previous dictatorial governments. To know the role that transitional justice plays in promoting human rights, it is necessary to know its concept and jurisprudential definitions found in some local laws, with the need to know the most important mechanisms and how to Applying it to work to correct a miserable past by revealing the truth of violations, knowing their perpetrators, and punishing them. Then, it is necessary to redress the victims’ harm and compensate them as a result of the violations they were exposed to, and reform the institutions that caused those violations, including the constitution, unfair laws, and the judicial structure. Emphasis is also placed on commemorating the violations in a manner that It enhances the role of transitional justice in promoting human rights.